PERSPEKTIF KOLABORATIF PENULISAN ARTIKEL ILMIAH PADA JURNAL MASYARAKAT BUDAYA TAHUN 2010 – 2019 - ROCHANI NANI RAHAYU; SENSUSIYATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Bibliometric research was conducted on the Journal of Society and Culture 2010-2019, with the aim of finding outL a) Number of articles published; (b) Number of articles per number of authors (c) Authorship patterns; (d) Degree of article collaboration (e) Collaboration between institutions;( f) Collaboration between universities; and (g) The most productive writer. The data was downloaded from http://jmb.lipi.go.id. The results showed the number of articles were 254 titles with 317 authors, so the average writer per article was 1.25. Articles written by a single author were 85.43%, and articles written in collaboration were 14.57%. The degree of collaboration is 1.54 on average. The institution where the author works is derived from 25 ministries and research institutions, as well as 42 from state / private tertiary institutions, and 4 overseas tertiary institutions (America, Taiwan, Australia). The most prolific writer is Robert Siburian with 7 articles, and comes from the LIPI Community and Cultural Research Center. It was concluded that the Journal of Society and Culture was not only in demand by LIPI researchers, but also in demand by researchers from institutions, private and foreign universities, with articles written by single authors dominating compared to articles written in collaboration.